The relationship between metabolic syndrome and environmental endocrine disruptors: a systematic review and meta-analysis - Pan, Kai; Xu, Jie; Li, Feng; Aris, Ahmad Zaharin; Yu, Huawen; Xu, Yuzhu; He, Jie; Wang, Chengxing; Yu, Jie (Elsevier, 2025)
Metabolic syndrome (MetS) is considered to be an important factor leading to an increased risk of chronic non-communicable diseases. Studies have found that exposure to environmental endocrine disruptors (EEDs) is associated with MetS, but the relationship between the two is unclear. In order to clarify the relationship between the two, a systematic review and meta-analysis were conducted to investigate their association. We searched Web of Science databases, Embase, and PubMed. We then utilized I2 statistics to assess the literature heterogeneity and pooled the data using both fixed-effects model (I2 < 50%) and the random effects model (I2 > 50%) in accordance with the PRISMA guidelines. The results showed that exposure to perfluoroalkyl substances (PFASs) was associated to specific components of MetS, such as PFNA and “high waist circumference” (OR = 1.23, 95% CI: 1.10–1.38), and PFOA and “elevated blood pressure” (OR = 1.05, 95% CI: 1.01–1.08). Exposure to phthalates (PAEs) increases the risk of MetS, with MECPP (OR = 1.16, 95% CI: 1.04–1.29) being an example. Moreover, polychlorinated biphenyls (PCBs) (OR = 1.47, 95% CI: 1.13–1.93) and organochlorine pesticides (OCPs) (OR = 1.97, 95% CI: 1.33–2.90) showed a positive association with the MetS. This study reveals that EEDs are a risk factor for MetS, which provides new evidence for the relationship between population EEDs exposure and MetS.